Пошаговое объяснение:
51.
1) 8целых 3/7 - 4целых 2/5 = 8целых 15/35 - 4целых 14/35 = 4целых 1/35
2) 6целых 11/15 - 2целых 7/10 = 6целых 22/30 - 2целых 21/30 = 4целых 1/30
3) 16целых 17/18 - 2целых 11/12 = 16целых 34/36 - 2целых 33/36 = 14целых 1/36
4) 18целых 13/48 - 5целых 3/64 = 18целых 52/192 - 5целых 9/192 = 13целых 43/192
53.
1) 8целых 3/4 - х = 3целых 5/16
х = 8целых 3/4 - 3целых 5/16
х = 8целых 12/16 - 3целых 5/16
х = 5целых 7/16
2) ( х - 9целых 3/7 ) + 5целых 8/21 = 6целых 5/14
х - 9целых 3/7 + 5целых 8/21 = 6целых 5/14
х + 5целых 8/21 = 6целых 5/14 + 9целых 3/7
х + 5целых 8/21 = 6целых 5/14 + 9целых 6/14
х + 5целых 8/21 = 15целых 11/14
х = 15целых 11/14 - 5целых 8/21
х = 15целых 33/42 - 5целых 16/42
х = 10целых 17/42
У=-62,4/3=-20,8
2)(3/4)х-(2/3)х+1=(1/2)х+1/6
(1/4)х-(2/3)х=1/6-1
(3-8)х/12=-5/6
(-5/12)х=-5/6
Х=2